(3GdEceGd aj PcQ ef dg QhGjI aj eSfO GdEeGe CMeO ef GdQLGd Shi ef PcQ aj JgPjH GdceGds - (3TeS GdOjf GHi GdeMGSf eMeO Hf Ydj Hf GdMSf Hf MeRg GdMSjf GdOeTbj GdeGdcjs; (3YHO GdQMef Hf YHO Gddg Hf CMeO GdNKYeqj GdSgjdqj,J (B581 (3g` s
(3ChdgG (B:s
(3hHYO aEfg deG bVi Gddg YR hLd ai GNJUGQ cJGH JgPjH GdceGd ai CSeGA GdQLGd s
(3BNQgG (B:s
(3YLhR ef Hfi fejQ CfgG SeYJ GdfHi Ydjg GdSdGe hgh jUdi HGdfGS hhLg Edi Je Je Je Je s
(3fSNI GNQis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs